Development, creation, and evaluation of puppetry program as an entertainment-education service of the city of Meycauayan Library - Sarza, Dominique Gabrielle R.; Apolinario, Rhea Rowena U. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
In a generation where anything is accessible through the internet, information is everywhere. Relevant information are transferred through news and articles – there are very few television shows nowadays that contain relevant information such as values and history in the Philippines. These kinds of information are usually featured in documentaries, news programs and movies that are most of the time appealing to adults. However, in the information profession world, there are various ways to disseminate information, depending on the age of the target audience. Puppetry, a form of entertainment-education, is among the tools contributing to a child’s learning and development but is rarely conducted in libraries.

The study sought to answer how the development of the puppetry program in the City of Meycauayan Library educate the children from Meycauayan City of information such as the kwentong bayan of the Meycauayan City. The study also aims to address how the involved citizens from the community view puppetry, and to answer how the development of the puppetry program affect the promotion of the City of Meycauayan Library.

The study created and developed a new program in the library, then afterwards, evaluated it. The researcher planned and conducted a puppet show in the library. The people who were involved- those who helped with the creation of the puppets, backdrops and the props; those who dubbed the story; those who manipulated the puppets- were all interviewed.

The study revealed that the children were able to comprehend the story of the alamat of Meycauayan through the use of puppetry. The people from the community who were involved proved to have the same and yet different perceptions on puppetry. All agreed that it is a very good program for the community, only differing on their views on how often it must be conducted, and of course, it has to be taken into account the availability of those who are willing to volunteer. Although seemingly difficult and impossible, conducting the puppet show in the library is possible and is an effective tool to disseminate information. There are many people from the community who are willing to be part of the program but one concern to be addressed is the lack of popularity of the library to the community.
Thesis
Keywords: Meycauayan City Library (Philippines); Public libraries -- Activity programs -- Philippines -- Meycauayan